Integration Object-Oriented Testing with UML: Integrating Object-Oriented Testing with UML (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Today's world is Object Oriented. In this Object Oriented world, we have Object-Oriented Languages, Object-Oriented Analysis, Deigning, and Testing of Softwares. From History, the foremost popular Object-Oriented modeling approaches are Rumbaugh's Object Modeling Technique (OMT), which was better for Object-Oriented Analysis (OOA), and Grady Booch's Booch method which was better for Object-Oriented Design (OOD). In 1994 OMT and Booch Method were unified into Unified Modeling Language (UML). Later on, in 1996, Object-Oriented Software Engineering (OOSE) also unified with UML.UML has synthesized the notation of Booch Method, the Object Modeling Technique, and Object-Oriented Software Engineering by fusing them into single and widely usable modeling language. Object-Oriented Testing remains separate. Therefore the thrust behind this paper is to integrate Object-Oriented Testing with UML.